2017
DOI: 10.1080/13545701.2017.1380309
|View full text |Cite
|
Sign up to set email alerts
|

Paid Maternity Leave and Breastfeeding in Urban China

Abstract: Using data from the 2010 Survey on Chinese Women's Social Status, this contribution estimates the effect of paid maternity leave on breastfeeding duration in urban China during the 1988-2008 period. The analysis applies a policy-based identification strategy to control for the endogenous relationship between paid leave entitlements and breastfeeding decisions. Estimates show that paid maternity leave has a strong positive effect on breastfeeding duration. Specifically, if the length of paid leave increases by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 23 publications
(25 reference statements)
1
17
0
Order By: Relevance
“…Because paid maternity leave protects women's employment and income during their pregnancy and after childbirth, the women are more likely to have better breastfeeding practices (Chai, Nandi, & Heymann, 2018;Rollins et al, 2016). Previous studies showed that mothers who returned to work were less likely to practice EBF (Jia, Dong, & Song, 2018;Mirkovic, Perrine, & Scanlon, 2016). Given that the duration of paid maternity leave in China is just 14 weeks, it is challenging for mothers to exclusively breastfeed their children for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Because paid maternity leave protects women's employment and income during their pregnancy and after childbirth, the women are more likely to have better breastfeeding practices (Chai, Nandi, & Heymann, 2018;Rollins et al, 2016). Previous studies showed that mothers who returned to work were less likely to practice EBF (Jia, Dong, & Song, 2018;Mirkovic, Perrine, & Scanlon, 2016). Given that the duration of paid maternity leave in China is just 14 weeks, it is challenging for mothers to exclusively breastfeed their children for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…China provides 128 days of paid family leave (Jia, Dong, & Song, 2018), and Russia provides 140 days of paid family leave (Addati, Cassirer, & Gilchrist, 2014;IBP, 2016). By comparison even though the US does not generally require this form of paid leave, U.S, employers could voluntarily choose to adopt a policy that would, and many have done so.…”
Section: Labor Laws In Different Countriesmentioning
confidence: 99%
“…As a reflection of the rural-urban divide, paid leave, to a large extent, remains an urban phenomenon. In the cities, the coverage of paid leave in private sectors, where migrant workers are concentrated, is low because there are no effective means of enforcing labor market regulations in these sectors (Jia, Dong, and Song 2018). In 2016, only 49.6% of the Chinese mothers who gave birth received maternity leave benefits, which is well below 82% in Mongolia and 69% in the Russian Federation.…”
Section: Public Support For Families and Working Womenmentioning
confidence: 99%